Academic leadership and governance of higher education : a guide for trustees, leaders, and aspiring leaders of two- and four-year institutions /: a guide for trustees, leaders, and aspiring leaders of two- and four-year institutions. (2023) - Harris, James T; Lane, Jason E; Sun, Jeffrey C; Baker, Gail Frances
No abstract available